Modern power system analysis - Gönen, Turan (CRC Press, 2013)
"This book offers a comprehensive coverage of all classical topics in power system analysis such as basic concepts of three AC circuits and per unit calculation, transmission line, power flow analysis, fault analysis and protection system etc. This second edition is a modern update of the book, which features clear and easy-to-understand text ideally suited for power system analysis courses at senior undergraduate level and graduate level."--Dr. Zhao Xu, The Hong Kong Polytechnic University, Hunghom, Kowloon" ... the book provides a fresh perspective."-Walid Hubbi, New Jersey Institute of Technology (NJIT), USA"This book is written specifically for the study of modern power systems with emphasis on power-transmission engineering. It introduces the reader to concepts and issues relevant to the power utility industry. ... In using this book, the reader will gain a very good understanding of power engineering fundamentals, from understanding and being able to use symmetrical component theory to writing MATLAB code for power-ftow analysis. This book is well written and has numerous illustrations and worked out examples to reinforce learning. The book could be used in a senior-level undergraduate class or graduate-level class in power engineering as well as by practicing engineers in a power utility or others who may want to teach themselves."--John J. Shea, IEEE Electrical Insulation Magazine